Acaricidal property of kuppaimeni (Acalypha indica) against natural Psoroptes cuniculi infestation in broiler rabbits - PRAKASH SINGH, D ANANDHA; RAMAN, M; SARADHA, V; JAYABHARATHI, P; SARAVANA KUMAR, V RAMESH (The Indian Journal of Animal Sciences, 2014)
The acaricidal property of Acalypha indica was evaluated in naturally Psoroptes cuniculi infested broiler rabbits for its in vitro (48 hr) and in vivo (14 days) activity based on livable mite count, lesion score and gross changes. The Acalypha indica paste had a lethal effect on the livable mites from 4 hr and maximum inhibition at 48 hr with prominent suppression of lesion. Regrowth ofhair in affected areas were prominently seen from 120 hr of treatment.